Urban furniture design - Nikoljski panevski, Elena; Tashkova, Emilija (My University, 2019)
For the purpose of this work is designed exterior furniture and urban equipment or set of exterior furniture arranging urban area (park, square). By analyzing this type of furniture and it’s needs there comes the need for design of several different pieces of furniture, including: chair (seating for one), two person bench, three person bench, flower pots, ambient lighting and bin. By analyzing outdoor furniture and its needs from material aspect there are certain reasons why there is use of oak wood for the first model of outdoor bench and thermo wood for the second model of outdoor bench. This paper analyzes what are the positive consequences of its use. In the process of designing it is starting from the square as a geometric most stable shape and its further development and integration in the shape of the outdoor furniture. The anthropometric standards observed for this type of furniture and the choice of material which should satisfy the requirements and needs of the desired look. The ultimate goal is to get a quality seating and leaving outdoor in which the human factor is very important. Through better understanding of the parameters of ergonomics, the designer can improve health and safety in furniture. Actually obligation and task of the planner is to constantly monitor research in the field of ergonomics to implement, maintain and improve the design of furniture.
Keywords: outdoor bench; lighting; litter bins; pot; construction; wood coatings